Phyllospheric fungal diversity in decomposing larch leaf litter: a comparative study of epiphytic and endophytic fungi - Pan, Hong; Wei, Dan; Yang, Libin; Fu, Xiaoyu; Zhu, Daoguang; Lu, Xinming; Liu, Siyuan; Liu, Yongzhi (Frontiers in Microbiology, 2024)
IntroductionEpiphytic and endophytic fungi are primary decomposers of forest litter due to their complex species composition and metabolic functions. To clarify the community diversity of phyllospheric fungi and to explore nutrient loss and the role of fungal decomposition, we conducted a study on the decomposition of leaf litter during the 1-year decomposition of Larix gmelinii in the cold temperate zone.MethodsFungal diversity data were characterized via Single Molecule Sequencing (based on the Sequel II Sequencing System) and statistical analyses in R.Results and discussionOur findings revealed the presence of 11 known fungal phyla and 29 dominant genera in the larch litter of Greater Khingan. Among these, Basidiomycota and Leucosporidium were dominant in the epiphytic environment, while Ascomycota and Exutisphaerella dominated the endophytic environment. In the early periods of decomposition, phyllospheric fungi became the primary colonizers during litter decomposition by adjusting their life strategies to transition to saprophytic or pathogenic metabolic processes. During decomposition, significant differences in alpha diversity were observed between endophytes and epiphytes. Correlation analysis between these fungi and biological factors revealed a strong relationship between cellulose loss in leaves and the return of N, P, and K. This indicated that the combined biological effects of nutrients, aminosugars, and plant fibers strongly explained changes in community structure. Our results also revealed a significant clustering effect between fungi and biological factors, reflecting the important role of phyllospheric functional fungal communities in carbon fluctuations, cellulose decomposition, and the enrichment of P and K in leaf litter. In summary, this study offers insights into ecosystem processes and nutrient cycling within cold temperate forests, with potential applications for understanding global carbon dynamics.